35th International Conference on Infrared, Millimeter, and Terahertz Waves 2010
DOI: 10.1109/icimw.2010.5613021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the dielectric substrate on the terahertz electric near-field of a hole in a metal

Abstract: Abstract:We have studied theoretically and experimentally the influence of a dielectric substrate on the frequency-dependent terahertz electric near-field of a small hole in a metal layer. We find that the near-field transmission spectrum and the two-dimensional field distribution of an empty hole in a thin metal layer on a substrate are almost identical to that of a hole which is also filled with the same dielectric material as the substrate. For thicker metal layers, however, the near-field spectra of filled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The horizontal white dashed lines indicate the positions at which the x-y cross sections in Figure 4 were taken -30 nm below the probe aperture and 130 nm below the dipoles. Only the non-zero field components are plotted in the figure . The simulated profiles in this section are in agreement with results obtained for goldcoated tapered fiber tips [29], a planar Bethe aperture [30] and a hole in a metal film at THz frequencies [31].…”
Section: Correspondence Between the Fields Of The Hollow-pyramid Prob...supporting
confidence: 84%
“…The horizontal white dashed lines indicate the positions at which the x-y cross sections in Figure 4 were taken -30 nm below the probe aperture and 130 nm below the dipoles. Only the non-zero field components are plotted in the figure . The simulated profiles in this section are in agreement with results obtained for goldcoated tapered fiber tips [29], a planar Bethe aperture [30] and a hole in a metal film at THz frequencies [31].…”
Section: Correspondence Between the Fields Of The Hollow-pyramid Prob...supporting
confidence: 84%
“…Visualizing the near-field close to metallic microstructures with subwavelength spatial resolution provides a unique way to study their response to light. In recent studies THz near-field microscopy was used to characterize electromagnetic field transmission through subwavelength apertures [13][14][15][29][30][31] or the complex interaction of metamaterials with light [16,20].…”
Section: B Resonant Excitation Of a Metallic Microwirementioning
confidence: 99%
“…To date, a range of studies have already demonstrated the potential of THz near-field imaging for the investigation of optical near-fields close to metallic structures, such as small apertures [13][14][15][16][17], or microresonators and metamaterials [18][19][20][21][22]. Here, we extend the scope of this approach by demonstrating how particularly the intrinsic phase-sensitivity of pulsed THz nearfield microscopy can be utilized to analyze the formation and propagation of electromagnetic waves close to metal micro-structures.…”
mentioning
confidence: 93%